Longitudinal development of anthropometric and physical characteristics within academy rugby league players - Till, K.; Jones, B.; Darrall-Jones, J.; Emmonds, S.; Cooke, C. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to evaluate the annual and long-term (i.e., 4 years) development of anthropometric and physical characteristics in academy (16-20 years) rugby league players. Players were assessed at the start of preseason over a 6-year period and were required to be assessed on consecutive years to be included in the study (Under 16-17, n = 35; Under 17-18, n = 44; Under 18-19, n = 35; Under 19-20, n = 16). A subset of 15 players were assessed for long-term changes over 4 years (Under 16-19). Anthropometric (height, body mass, sum of 4 skinfolds) and physical (10- and 20-m sprint, 10-m momentum, vertical jump, yo-yo intermittent recovery test level 1, 1 repetition maximum [1RM] squat, bench press, and prone row) assessments were collected. Paired t-tests and repeated measures analysis of variance demonstrated significant annual (e.g., body mass, U16 = 76.4 ± 8.4, U17 = 81.3 ± 8.3 kg; p < 0.001, d = 0.59) and long-term (e.g., vertical jump, Under 16 = 44.1 ± 3.8, Under 19 = 52.1 ± 5.3 cm; p < 0.001, d = 1.74) changes in anthropometric and physical characteristics. Greater percentage changes were identified between the Under 16-17 age categories compared with the other ages (e.g., 1RM squat, U16-17 = 22.5 ± 19.5 vs. U18-19 = 4.8 ± 6.4%). Findings demonstrate the annual and long-term development of anthropometric and physical characteristics in academy rugby league players establishing greater changes occur at younger ages upon the commencement of a structured training program within an academy. Coaches should understand the long-term development of physical characteristics and use longitudinal methods for monitoring and evaluating player performance and development.